Eating disorders and self-image perception (Research, Society and Development, 2020)
The present study has as its theme the link between the perception of self-image and eating disorders. In this sense, the objective was to demonstrate through articles related to the theme how effectively eating disorders reflect on people's lives through perception, as well as verifying that there are significant influences on the daily lives of these individuals and the way they present themselves and recognize their reality. The methodology used was the integrative review method, with surveys carried out between February and April 2020, which aimed to find works on the topic, filtering the research that would be relevant, excluding those that were not necessary and aligning those that would be used in the study. In the course of this research, it was possible to verify that in many cases the perception of self-image can cause damage to health and consequently serious problems, such as: disorders related to bulimia, anorexia and binge eating. The results of the collected data indicated that the perception of self-image associated with external factors considerably influences the occurrence of eating disorders, affecting mainly women, adolescents, young people and adults. In addition, it was found that eating disorders related to the perception of self-image are psychic disorders. Thus, it was concluded that the nutritional assessment of each individual is of paramount importance and the first step to demonstrate for the same that the image built by him does not always reflect the healthy and ideal reality.